The geographical position of the town of Rasa based on Porphyrogenitus and medieval maps - Grčić, Mirko; Grčić, Ljiljana; Sibinović, Mikica (Acta geographica Slovenica, 2018)
The town of Rasa was mentioned in the tenth-century work De administrando imperio by Constantine VII Porphyrogenitus. The significance of this town in the Middle Ages is indicated by the fact that this toponym appears on old maps created by the greatest European cartographers from the fifteenth to nineteenth centuries. Based on cartographic and historical geographical sources, this paper considers various perceptions and texts connecting the town of Rasa with today’s town of Ražanj or with the medieval Serbian capital Ras. The subject treated is historical social geography. Five types of sources were used for the historical geography of the Balkans: old maps, chronicles, geographical nomenclature, archeological findings, and ethnographic findings. Based on written sources, geographical names, and geographical logic, the authors provide their own conclusions about the geographical position of the town of Rasa.